2016
DOI: 10.1039/c6ta04737h
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dots with tunable concentrations of trapped anti-oxidant as an efficient metal-free catalyst for electrochemical water oxidation

Abstract: Carbon dots, containing keto-groups as active sites and the highest abundance of an anti-oxidant, 5-hydroxymethyl-2-furaldehyde, efficiently catalyse oxygen evolution reaction in alkaline medium and generate 10 mA cm−2at 0.21 V overpotential..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 69 publications
(95 reference statements)
0
36
0
Order By: Relevance
“…The disappearance of carbonyl (C=O) group in both 1 H and 13 C NMR of WACDs suggested that water dispersibility of ACDs may be due to the hydrogen bonding. It is already reported that the chemical shift of ACDs in the range of 175–180 ppm ( 13 C NMR) demonstrated the presence of the furfural based environment in CDs . The chemical shift of ACDs in the range of 5–7.5 ppm ( 1 H NMR) and 165–170 ppm ( 13 C NMR) may be ascribed to the existence of the aromatic group in carbon dots.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The disappearance of carbonyl (C=O) group in both 1 H and 13 C NMR of WACDs suggested that water dispersibility of ACDs may be due to the hydrogen bonding. It is already reported that the chemical shift of ACDs in the range of 175–180 ppm ( 13 C NMR) demonstrated the presence of the furfural based environment in CDs . The chemical shift of ACDs in the range of 5–7.5 ppm ( 1 H NMR) and 165–170 ppm ( 13 C NMR) may be ascribed to the existence of the aromatic group in carbon dots.…”
Section: Resultsmentioning
confidence: 86%
“…However, no chemical shift in WACDs is observed in the range of 8.5–10 ppm for disappearance R‐CHO the protons. Figure C show 13 C NMR spectra displaying chemical shifts in ACDs in the regions of ∼10–40 ( sp 3 hybrids carbons), 40–80 (different functional group attached with carbon such as hydroxy R‐OH, ether R−O‐R, and carbonyl R‐C=O), 100–170 (sp 2 hybridized aromatic or C=C sp 2 carbons), and 170–210 ppm (carbonyl (C=O) carbons) groups ,. In contrast to ACDs, no chemical shift in the range of 170–210 ppm in WACDs indicated the complete disappearance of C=O carbons.…”
Section: Resultsmentioning
confidence: 99%
“…5 The need of the hour is to develop an earth-abundant pHuniversal HER catalyst that can trigger proton reduction with Pt-like fast kinetics and the least possible overpotential. A rejuvenated self-supported electrode is even more attractive as it allows skipping polymeric binders that block catalytically active sites, 28 and avoiding additional current collectors such as the glassy carbon electrode (GCE), 29 carbon ber paper (CFP), 30 carbon cloth, 31 and Ni or Cu foam. [32][33][34] Rational design of selfsupported electrodes is critically dependent on a fairly large exposed surface, enhanced mass diffusion and efficient electron transport with futuristic applications towards wearable and exible energy devices.…”
Section: Introductionmentioning
confidence: 99%
“…The QY of the CDs was measured at an excitation wavelength of 360 nm using quinine sulfate as a standard (QY = 54%) [ 6 ]. Confocal microscopy analysis was performed using an Olympus FluoView 500 laser scanning confocal microscope (Olympus, Tokyo, Japan), and the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay of the obtained CDs was used to quantify the viability of HeLa cells [ 40 ].…”
Section: Methodsmentioning
confidence: 99%